Students’ Agency in a Foreign Language Policy in Colombian Higher Education - Sergio Lopera; Nelly Sierra (Profile Issues in Teachers' Professional Development)
This qualitative ethnographic study investigates students’ agency of a language policy in a Colombian public university. Participants were 85 undergraduate students, and data collection involved document analysis, non-participatory observation, a questionnaire, and a portfolio. Three categories emerged from the analysis: acceptance, rejection, and ignoring. Regarding acceptance, the findings suggest that some students agreed with including English in the curriculum. Some other students expressed rejection related to the English class, the methodology, the evaluation proposal, and the course material. Other students ignored elements regarding their own role in the program, extra-class activities, and participation and attendance in class. Conclusions indicate that students are not passive recipients of language policies because they exercise agency differently at the micro level.